Data for "Computational Design of Alloy Nanostructures for Optical Sensing of Hydrogen" - Pernilla Ekborg-Tanner; J. Magnus Rahm; Victor Rosendal; Maria Bancerek; Tuomas P. Rossi; Tomasz J. Antosiewicz; Paul Erhart (Chalmers University of Technology, 2022)
This record contains data pertaining to the publication "Computational Design of Alloy Nanostructures for Optical Sensing of Hydrogen".
Keywords: Physical Sciences; Fysik